ANALISIS PREFERENSI PELAKU USAHA MIKRO DALAM MENGGUNAKAN PEMBIAYAAN MIKRO SYARIAH (Studi Kasus: Usaha Mikro di Batang Gadih Kecamatan Batipuh Baruh Kabupaten Tanah Datar) - Rezzi Mulia Irwan; Cahya Agung Mulyana (Jurnal Ekonomi dan Bisnis, 2025)
This research is motivated by several obstacles experienced by micro business actors, including a lack of education and promotion, a lack of understanding of the concept and its benefits, and the public's tendency to choose conventional banks. The aim of this research is to find out and analyze micro business actors in Batang Gadih, Batipuh Baruh sub-district in using sharia micro financing. The method used in this research is a qualitative descriptive method carried out by direct observation of micro business actors in Batang Gadih to obtain data that suits the problem. The data collection techniques used in this research were observation, interviews and document study. Meanwhile, the data analysis technique used in this research is the theory of business actor preferences, using 3 factors, namely environmental factors, personal factors and psychological factors. The research results show that the decisions of micro business actors in Batang Gadih, Batipuh Baruh District, in choosing sharia micro financing are influenced by three main factors, namely environmental, personal and psychological factors. Environmental factors emphasize the alignment of sharia financing with local ethical values and social norms. Personal factors demonstrate the importance of lifestyle and business practices that are in line with sharia principles, such as honesty and transparency. Meanwhile, psychological factors reflect the comfort and identity of business actors in using halal financing.